Overview of Binocular Diplopia: Etiology, Assessment Methods, and Treatment Strategies - Yasir Adil Shakor; Razieh Bahreini; Ali Majdi (Journal of Modern Rehabilitation)
Binocular diplopia is a challenging oculomotor disorder that significantly impacts patients’ quality of life. This review provides a comprehensive overview of the etiology, diagnostic methods, and treatment strategies for binocular diplopia. Proper diagnosis begins with differentiating between monocular and binocular diplopia, followed by determining whether the cause is motor or sensory. Diagnostic methods include detailed medical history, qualitative and quantitative assessment of diplopia, analysis using tools like the Haab Grid, evaluation of ocular motility, and assessment of head postures. The level of oculomotor defect should be investigated to differentiate between nuclear and supranuclear lesions. Treatment approaches are diverse and depend on the underlying cause. Functional strategies may include prismatic correction, which can provide immediate relief from diplopia. Surgical interventions are considered for cases of paralytic strabismus or when conservative measures are insufficient. The choice of treatment is guided by factors, such as the etiology, duration, and severity of diplopia. Prismatic correction is often used as both a diagnostic tool and a treatment option, allowing for precise adjustment of eye alignment. In cases of acute diplopia, a systematic approach to diagnosis and appropriate identification of possible causes enables better patient management. This comprehensive approach to binocular diplopia, encompassing thorough diagnostic methods and a range of treatment strategies, improves functional outcomes and enhances the quality of life for affected patients. This study emphasizes the complexity of diplopia, distinguishing between monocular and binocular types, and motor and sensory forms. Management involves functional therapies, prismatic correction, and if needed, botulinum toxin or surgery. Prompt evaluation and multidisciplinary collaboration are essential, particularly for neurological causes.